Neurotransmitters and Neuropeptides decrease PD-1 in T cells of healthy subjects and patients with hepatocellular carcinoma (HCC), and increase their proliferation and eradication of HCC cells. (October 2021) - Levite, Mia; Safadi, Rifaat; Milgrom, Yael; Massarwa, Muhammad; Galun, Eithan
Abstract: T cells of aged people, and of patients with either cancer or severe infections (including COVID-19), are often exhausted, senescent and dysfunctional, leading to increased susceptibilities, complications and mortality. Neurotransmitters and Neuropeptides bind their receptors in T cells, and induce multiple beneficial T cell functions. Yet, T cells of different people vary in the expression levels of Neurotransmitter and Neuropeptide receptors, and in the magnitude of the corresponding effects. Therefore, we performed an individual-based study on T cells of 3 healthy subjects, and 3 Hepatocellular Carcinoma (HCC) patients. HCC usually develops due to chronic inflammation. The inflamed liver induces reduction and inhibition of CD4 + T cells and Natural Killer (NK) cells. Immune-based therapies for HCC are urgently needed. We tested if selected Neurotransmitters and Neuropeptides decrease the key checkpoint protein PD-1 in human T cells, and increase proliferation and killing of HCC cells. First, we confirmed human T cells express all dopamine receptors (DRs), and glutamate receptors (GluRs): AMPA-GluR3, NMDA-R and mGluR. Second, we discovered that either Dopamine, Glutamate, GnRH-II, Neuropeptide Y and/or CGRP (10nM), as well as DR and GluR agonists, induced the following effects: 1 . Decreased significantly both %PD-1 + T cells and PD-1 expression level per cell (up to 60% decrease, within 1 h only); 2. Increased significantly the number of T cells that proliferated in the presence of HCC cells (up to 7 fold increase), 3. Increased significantly T cell killing of HCC cells (up to 2 fold increase). 4 . Few non-conventional combinations of Neurotransmitters and Neuropeptides had surprising synergistic beneficial effects. We conclude that Dopamine, Glutamate, GnRH-II, Neuropeptide Y and CGRP, alone or in combinations, can decrease % PD-1 + T cells and PD-1 expression per cell, in T cells of both healthy subjects and HCC patients, and increase their proliferation in response to HCC cells and killing of HCC cells. Yet, testing T cells of many more cancer patients is absolutely needed. Based on these findings and previous ones, we designed a novel "Personalized Adoptive Neuro-Immunotherapy", calling for validation of safety and efficacy in clinical trials.